Energy, economic, and environmental analysis of integration of thermal energy storage into district heating systems using waste heat from data centres. (15th March 2021) - Li, Haoran; Hou, Juan; Hong, Tianzhen; Ding, Yuemin; Nord, Natasa
Abstract: Data centres produce waste heat, which can be utilized in district heating systems. However, the mismatch between data centres' heat supply and district heating systems' heat demands limits its utilization. Further, high peak loads increase the operation cost of district heating systems. This study aimed to solve these problems by introducing thermal energy storages. A water tank and a borehole thermal energy storage system were selected as the short-term and long-term thermal energy storage, respectively. Energy, economic, and environmental indicators were introduced to evaluate different solutions. The case study was a campus district heating system in Norway. Results showed that the water tank could shave the peak load by 31% and save the annual energy cost by 5%. The payback period was lower than 15 years when the storage efficiency remained higher than 80%. However, it had no obvious benefits in terms of mismatch relieving and CO2 emissions reduction. In contrast, the borehole thermal energy storage increased the waste heat utilization rate to 96% and reduced the annual CO2 emissions by 8%. However, the payback period was more than 17 years. These results provide guidelines for the retrofit of district heating systems, where data centres' waste heat is available. Highlights: Evaluate TESs in terms of energy, economic, and environmental indicators. Joint management of mismatch relieving and peak load shaving of TESs. Sensitivity study of storage efficiency to draw generalized conclusions. Water tank has better peak load shaving effect and shorter payback period. BTES increases waste heat utilization rate and reduces CO2 emissions.